2020
DOI: 10.31083/j.jin.2020.03.25
|View full text |Cite
|
Sign up to set email alerts
|

Early tracheostomy is associated with better prognosis in patients with brainstem hemorrhage

Abstract: Brainstem hemorrhage is presumed to be invariably associated with a poor prognosis in people with spontaneous hypertensive cerebral hemorrhage. The optimal timing of tracheostomy placement in brainstem hemorrhage patients, who generally require endotracheal intubation for airway protection, remains uncertain. Our research aim was to analyze the impact of early tracheostomy versus late tracheostomy on brainstem hemorrhage patients related outcomes and prognostic factors at 30 days. We identified early tracheost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Chen et al investigated 425 patients with hemorrhagic stroke and concluded that early TT in those patients could reduce hospital costs and hospital stays with no increase in hospital mortality (4). In another study, Ding et al claimed that early TT could improve the prognosis at 30 days in patients with brainstem hemorrhage (5). However, there are few studies focusing on postoperative TT in aSAH patients specifically (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al investigated 425 patients with hemorrhagic stroke and concluded that early TT in those patients could reduce hospital costs and hospital stays with no increase in hospital mortality (4). In another study, Ding et al claimed that early TT could improve the prognosis at 30 days in patients with brainstem hemorrhage (5). However, there are few studies focusing on postoperative TT in aSAH patients specifically (24).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with hemorrhagic stroke, the rates of TT have been found to be significantly higher than in non-neurologic patients (3). Also, several retrospective studies confirmed that the timing of TT could have significant effects in outcomes of patients with hemorrhagic stroke (4,5). Previously, the feasibility, safety, and reduction of sedation need of early TT in ventilated stroke patients have been confirmed in a randomized pilot trial (6).…”
Section: Introductionmentioning
confidence: 97%
“…However, whether age or sex affects patients with PBSH remains an unresolved problem. Patient age was found to independently affect 30-day mortality or functional outcomes by Morotti et al and Ding et al by multivariate logistic regression analysis (1,22). Intriguingly, no study has demonstrated that sex is a predictor of the outcomes of PBSH.…”
Section: Demographic Factorsmentioning
confidence: 97%
“…Central hyperthermia is a complication after PBSH that is characterized by a core temperature of ≥39 • C and is unresponsive to conventional antipyretic treatments due to an unchanged thermoregulatory setpoint (26)(27)(28). Central hyperthermia was proven to be independently related to death in PPH by Matsukawa et al, but was not identified as an independent predictive factor of 30-day outcomes after PBSH in another study (20,22). Although central hyperthermia associated with PBSH is supposed to be injurious to patients, it remains unknown whether a positive pursuit of a normal body temperature contributes to a more favorable clinical prognosis in the absence of evidence.…”
Section: Clinical Presentationsmentioning
confidence: 99%
See 1 more Smart Citation